Orientasi Wirausaha dan Kinerja Umkm: Efek Mediasi Dari Akses Keuangan dan Keunggulan Kompetitif - Agus Wicaksono; Suci Atiningsih (ECONBANK: Journal of Economics and Banking, 2021)
This study aims to analyze the effect of Entrepreneurial Orientation (Innovation, Risk Taking, Proactive) on MSME Performance; The mediating effect of Financial Access and Competitive advantage based on the direct and indirect subsections of Entrepreneurial Orientation. The object of this research is Culinary SMEs in Grobogan. Data were obtained from 84 samples of Culinary SMEs in Grobogan which were taken by accidental sampling. The data analysis technique used in thisresearch is SEM-PLS. The results of this study indicate that Risk Taking and Proactive have a positive effect on MSME Performance. While innovation does not affect the performance of SMEs. Innovation and Proactive have a positive effect on Financial Access, while Risk taking has no effect on Financial Access. Access to Finance has a positive effect on Competitive Advantage, and Competitive Advantage has a positive effect on MSME Performance). Financial Access and Competitive Advantage are able to mediate the relationship between proactiveness and MSME performance, but are unable to mediate the relationship between innovation and risk taking with the performance of culinary MSMEs in Grobogan.